The incidence of postoperative infection in tertiary rural hospital - Chawada, Meghraj; Nisale, Shobha S.; Kharkate, Ganesh K.; Deshmukh, Sudhir B. (International Surgery Journal, 2017)
Background: Post-operative wound infections have been a problem since surgery was started as a treatment modality. Post-operative infections were responsible for 70-80% of deaths until Ignaz Semmelweis and Joseph Lister, in middle of 19th century, introduced methods of infection control by use of antiseptics. Objective was to study the incidence of postoperative infection in tertiary rural hospital. Methods: A hospital based cross sectional study was carried out at Department of General Surgery, SRTR Rural Government Medical College from September 2015 to August 2016 among 1250 patients. Detailed history, complete and thorough clinical examination was carried out for each and every individual included in the present study. The patients are assessed pre operatively and post operatively. Results: It was found that the maximum cases belong to the age group of 26-35 years i.e. 28.32% followed by age group of 36-45 years (25.68%). The proportion of males was slightly more than females. The most common surgical procedure done was inguinal hernioplasty in 24.96% of cases followed by internal appendectomy in 22.24% of cases. Maximum study subjects had clean surgical procedure in 62.08% of cases. The highest incidence (19.46%) was found in the age group of above 56 years followed by age more than 56 years in 19.46% of cases. It was found that the incidence of SSI was more among females than males. It was found that the incidence of SSI was more among those with some co-morbidity than among those who doesn’t have any co-morbidity. Conclusions: Surgical infections particularly, surgical site infections, have always been a major complication of surgery and trauma. The overall prevalence of surgical site wound infection in the surgical ward was 10.4%.